Social media impact on cosmetology students in enhancing makeup techniques ability and their character building - Maida, Andi Nur; Burhanuddin, Izmi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
Social media with various platforms offered has become an integral part for the millennial generation which is currently used as a means of expressing themselves, obtaining information, communicating, learning and sharing stories of experiences and becoming a place to complain so that in the process this social media will continue to play an important role in the future. This study is a type of quantitative research that aims to find out (1) The description of social media in the makeup techniques of makeup students (2) Description of character formation of make-up students (3) The impact of social media on make-up techniques in the formation of character of make-up students, Family Welfare Education Department, Faculty of Engineering, Makassar State University, with a research sample of 39 students taken . based on simple random sampling method . Data collection techniques used is observation , documentation and questionnaires ( surveys ). Data analysis techniques using analysis descriptive , prerequisite test analysis and analysis test simple linear regression . Research results shows that (1) The description of the use of social media in the make-up techniques of make-up students with indicators of user frequency, type of content, make-up techniques and cosmetic products in general is described in the high category 48.72% ( 2) The description of the formation of the character of make-up students based on character formation with indicators of self-confidence, discipline, honesty, and responsibility in general is described in the moderate category 51.29% (3) The impact of social media in make-up techniques on the formation of character of make-up students in the Family Welfare Education Department, Faculty of Engineering, Makassar State University that the magnitude of the influence of social media in make-up techniques can be seen from the results of a simple regression analysis, the calculation results show F count = 279.175 with Sig. 0.000, then the test is significant at the significance level Î± = 0.05. The calculation results show t count = 16.709 with Sig. 0.000, then the test is significant at the significance level Î± = 0.05. The conclusion is that the perspective, attitude, patience, self-confidence of students sometimes do not match the expectations and desires seen on social media, so that it greatly influences the makeup techniques applied, but the responsibility, discipline of students and character need to be improved.